Computational modelling and sequence analysis provide new insights into the structure, function, and evolution of the pirB Gene in Photorhabdus, Xenorhabdus, and Vibrio species - de Guia, Arren Christian M; Uy de Guia, Mary Rose D; Alcantara, Simon G; Mingala, Claro N (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: To compare the structural and functional variations in the Photorhabdus insect-related B (pirB) genes of selected bacterial species such as Photorhabdus luminescens, Xenorhabdus doucetiae, and Vibrio parahaemolyticus. Materials and Methods: The study implemented phylogenetic analysis, three-dimensional (3D) structural modelling, and functional motif analysis of the pirB gene of three bacterial genera. Inferred evolutionary relationships as well as functional and structural differences were drawn based on the generated topology of the Neighbor-Joining (NJ) Tree and genetic analysis of protein sequences, domain structures, and functional motifs. Results: Phylogenetic analysis and NJ tree topology revealed close evolutionary affinity of Photorhabdus spp. and Xenorhabdus spp. This is possibly due to their known shared ecological niche as insect pathogens and nematode symbionts. In contrast, the known shrimp pathogen, V. parahaemolyticus remarkably showed significant divergence and clustered out from the clade of Photorhabdus and Xenorhabdus. This can be attributed to the adaptive changes in a marine environment, since V. parahaemolyticus is a known marine bacterium. The constructed 3D protein structures of pirB exhibited conserved transmembrane helices essential for membrane interaction. Species-specific adaptation was also evident in the generated pirB 3D model of V. parahaemolyticus. A unique structural element that confers resistance to environmental stresses was also observed. Analysis of functional motifs depicted evolutionary conservation in membrane interaction domains. Species-specific variations that may reflect adaptations to different host environments and pathogenic strategies were also predominant. Conclusion: The study provided valuable insights into the structure, function, and evolution of the pirB gene of three examined bacterial genera. This can be linked to evolutionary and selective pressures that led to the current pathogenicity of the pirB gene, with potential applications in public health, pharmaceuticals, agriculture, and fisheries. J. Adv. Vet. Anim. Res., 12(3): 1051–1058, September 2025 http://doi.org/10.5455/javar.2025.l965